Visual Tree Assessment (VTA) of Tree Health in the Green Belt of Southern Ring Road, Mataram City - Muhammad Rafly Lanang Pamungkas; Andi Tri Lestari; Irwan Mahakam Lesmono Aji (Masyarakat Peneliti Kayu Indonesia, 2025)
Green belts play a crucial role in urban green spaces by providing shades, filtering air pollutants, and enhancing city aesthetics.This study aims to evaluatethe health condition of trees along the South Ring Road green belt in Mataram City using the Visual Tree Assessment (VTA) method. VTA assesses tree vitality and structural stability based on observable external indicators, such as cracks, swellings, and crown asymmetry. A census approach was applied to a total of 1,432 trees. The results revealed that 77% of the trees were categorized as low risk, 21% as moderate risk, and 2% as high to extreme risk. The most common types of defects observed included stem cankers, dead branches, and decay. Recommended management actions include regular pruning, selective felling, the use of biological pesticides, and relocation of severely affected trees. This research provides a valuable foundation or developing effective tree risk management strategies in urban environments..